SISTEM ABSENSI GURU DAN STAFF BERBASIS WEB - Adhira Maharani Putri; Wahyuni; Rival Fahrezi Saputra; Wasis Haryono (Journal of Research and Publication Innovation, 2025)
Vocational High School (SMK) YAPIA Parung is a private school located in Waru Jaya Village, RT 01/03, Parung District, Bogor Regency. Currently, the school still uses a conventional attendance system, which can certainly be improved to a more modern system. The researcher conducted a study by developing a web-based school attendance system to achieve more accurate and efficient results. The writer also applied the SCRUM method and utilized QR Code technology, which is expected to simplify user interaction. The results of the study showed that the implementation of a web-based attendance system was able to facilitate teachers and staff in recording attendance and monitoring presence in real-time. It can be concluded that the web-based attendance system has proven to be more effective and user-friendly for staff and teachers compared to the previously used conventional method.